THE RELATIONSHIP BETWEEN TRIAGE USING EWS SCORES AND NURSES’ RESPONSE TIME IN EMERGENCY PATIENT MANAGEMENT AT IGD RSU ABDHI FAMILI BANYUWANGI - Aziz, Aditya Nuraminudin; Prawito (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: The Emergency Department (IGD) is a vital unit in a hospital that provides first aid to emergency patients. The application of the Early Warning System (EWS) in the emergency room triage process is very crucial as a parameter for monitoring and early detection of critical conditions. Objective: This study aims to analyze the relationship between emergency room triage using EWS score and nurse response time in handling emergency patients at Abdhi Famili Banyuwangi Hospital. Methods: This research employed a correlational analytic design with a cross-sectional approach. The population and sample consisted of all nurses working in the Emergency Room of Abdhi Famili Banyuwangi Hospital, totaling 30 participants, selected through total sampling. Data were collected using observational instruments. Results: The results showed that of the 18 respondents with low EWS scores, the majority (13 people or 72.2%) had a fast response time. The analysis using the Spearman Rank test yielded a value of p = 0.047 (< α = 0.05) and a correlation coefficient of 0.365. A p-value of less than 0.05 showed a significant relationship between emergency room triage using EWS scores and nurses' response time in handling emergency patients. However, a correlation coefficient value of 0.365 indicates that the relationship falls into the low category. Conclusion: There was a significant relationship, although in the low category, between emergency room triage using EWS scores and nurses' response time in handling emergency patients at Abdhi Famili Banyuwangi Hospital.